UNDERSTANDING BOURDIEU’S DISTINCTION: SOCIAL AND LITERARY CONTESTATION TO GAIN LEGITIMATE POSITION - Ghanesya Hari Murti; Nila Susanti (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2021)
This writing reveals the subtle domination in the area of literature and social practice which is illustrated through the practice of coffee consumption and also the claims of legitimate authors. Bourdieu examines this sociological space as a field of contestation, so he constructs his sociological project by mapping the type of social power in arena in which every subject wagers his capital to achieve a legitimate position. In the arena, each subject desires to get power either by way of embracing the rule that applies, doxa, or to fight with the practice of the new, heterodox. Following the existing rules are not able to change anything because it dictates the subject to be a disciplined subject. Bourdieu proposes the emerging heterodox because doing resistance to all forms of domination can give birth to the new alternative social structure and preventing the old one to remain in power. Social change is expected because Bourdieu's symbolic power as in symbolic capital tends to provoke symbolic violence. Having symbolic capital enchanting for its power to subtly dominate people with less capital. Oppression becomes natural due to everyday practice normalizing the oppression. shapes the taste of a certain class as class distinction. Bourdieu’s concept of distinction investigates a more sophisticated strategy in the social arena where every agent plays subtle intimidation and indeed domination.